Developing Student Leadership Readiness, Core Leadership Skills to Enhance Student Engagement through Organization Development Intervention: Action Research at Zhejiang Yuexiu University of Foreign Languages in Zhejiang Province, the People’s Republic of China - Li, Bing; Kim, Seongdok (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
Student leadership development has captured increasing concern in the field of education. Leadership plays an integral part in the fulfillment of 21st-century skills, namely, career and life skills, to adapt to the changing circumstances and the need to cultivate talent. The present action research aimed to utilize effective OD interventions to develop students’ leadership readiness and core leadership skills to enhance student engagement in campus-based extracurricular activities in a private university in China. The action research was conducted in three stages: Pre-ODI, ODI, and post-ODI, starting with diagnosing problems in student leadership, followed by planning, intervening, assessing, and reinforcing. For the eight-month OD intervention, the sample consisted of 80 freshmen randomly selected from the student organization. They were categorized into two groups: an experimental group with ODIs and a control group without ODIs. Data were collected by survey questionnaires, one-to-one interviews, and focus group interviews, using qualitative and quantitative research methodology. Results of the Paired Sample T-Test proved that there were statistically significant differences between the experimental group and the control group after ODIs. Students reported significant gains in leadership readiness and core leadership skills. There was a causal relationship among leadership readiness, core leadership skills, and student engagement. The results of the research suggest that purposeful leadership programs should be promoted in the form of offline and online extracurricular activities to cultivate leadership competency beginning with inward leadership and manifesting in outward leadership.